2010
DOI: 10.1016/j.exer.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Multilamellar spherical particles as potential sources of excessive light scattering in human age-related nuclear cataracts

Abstract: The goal of this project was to determine the relative refractive index (RI) of the interior of multilamellar bodies (MLBs) compared to the adjacent cytoplasm within human nuclear fiber cells. MLBs have been characterized previously as 1-4 μm diameter spherical particles covered by multiple lipid bilayers surrounding a cytoplasmic core of variable density. Age-related nuclear cataracts have more MLBs than transparent donor lenses and were predicted to have high forward scattering according to Mie scattering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…During cataractogenesis, formation of high molecular mass (HMM) aggregates cause fluctuations in protein density, resulting in light scattering and a concomitant decrease in transparency. Other factors such as multilamellar bodies and morphological changes could also contribute substantially to lens opacity [15][16][17][18] and not compaction [19]. The organellefree cytoplasm of the lens nuclear fiber cell is one such component that contains vital information about the packing and organization of crystallins critical to lens transparency.…”
Section: Cataract Disorder and Some Physico-chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…During cataractogenesis, formation of high molecular mass (HMM) aggregates cause fluctuations in protein density, resulting in light scattering and a concomitant decrease in transparency. Other factors such as multilamellar bodies and morphological changes could also contribute substantially to lens opacity [15][16][17][18] and not compaction [19]. The organellefree cytoplasm of the lens nuclear fiber cell is one such component that contains vital information about the packing and organization of crystallins critical to lens transparency.…”
Section: Cataract Disorder and Some Physico-chemical Propertiesmentioning
confidence: 99%
“…The published work to Metlapally et al [19] has provided analysis of the cytoplasmic texture to transparent and advanced cataractous lenses and related the extent of texturing to the nuclear scattering observed using the Debye-Bueche theory for inhomogeneous materials. The extent of forward scattering and its influence on macular visual acuity could be important components of ophthalmological evaluations of cataract patients [16]. Filipin cytochemistry in combination with freeze fracture revealed that the amount of cholesterol in the normal fibre membranes was fully comparable with the amount of cholesterol in the deviating membranes of the focal opacities and the multilamellar bodies [17].…”
Section: Cataract Disorder and Some Physico-chemical Propertiesmentioning
confidence: 99%
“…1). Hence, resulting m 1 = n l /n m = n i /n lb = 1.49/1.5 and m 2 = n l /n m = n lb /n c = 1.5/1.42 (relative refractive indices of the first and the second layer, respectively) [4,6]. The characteristics of scattering are essentially controlled by simple factors (r, λ , m l ).…”
Section: Effect Of Light Scattering Due To Multilamellar Bodies In Thmentioning
confidence: 99%
“…When photons pass through MLBs formed by layers with a refractive index different from the core of the MLBs, the scattering angle range increases even more and hence the forward scattering decreases. In research done by Costello [4,6,7], the MBLs are considered to be potential sources for excess light scattering in age-related nuclear cataracts and described likely candidates for large scattering particles. Thus, to be considered as large particles suggested that their major contributions would be low-angle scattering owing to their lipid-rich layer and fluctuations in the cytoplasm might be responsible for key fluctuations in the local refraction index essential to produce significant light scattering.…”
Section: Ifmbe Proceedingsmentioning
confidence: 99%
See 1 more Smart Citation